Pengaruh Pemahaman Otoritas Narasi terhadap Keterampilan Menulis Teks Deskripsi pada Siswa Kelas VII Madrasah Tsanawiyah Muallimin Universitas Al Washliyah Medan Tahun Ajaran 2025–2026 - Marchanda Rizalni; Susy Deliani; Nurhayati Nurhayati (Universitas Islam Sumatera Utara, 2026)
This study examines the influence of students’ understanding of narrative authority on their ability to write descriptive texts among seventh-grade students at Madrasah Tsanawiyah Muallimin Universitas Al Washliyah Medan in the 2025–2026 academic year. The research is grounded in the limited pedagogical variation observed in classroom practices, where teachers tend to rely heavily on textbook-based instruction without adequately developing students’ narrative competence. The study addresses the question of whether enhancing students’ understanding of narrative authority significantly improves their descriptive writing skills. A quantitative experimental approach was employed using a two-group pretest-posttest design. From a population of 300 students, 60 were selected through random sampling and divided into experimental and control groups. Hypothesis testing was conducted using an independent samples t-test. The results indicate that the experimental group achieved a mean score of 61.5, while the control group obtained a mean of 43. The calculated t-value (2.851) exceeded the critical value, indicating a statistically significant effect. The findings demonstrate that a stronger understanding of narrative authority contributes positively to students’ descriptive writing proficiency.